Porous Emerald - Lindborg, PerMagnus (2017)
Jago stirs: something is strange. Ice-cold wind streams from the aircon and relentless chatter from the radio: "…it would not be without reason to deem it a ghost or a phantom formed by the brain…"1 Reality blur: yes, he must have drifted off. Yes, the taxi, but no, why have we stopped? What time is it? He breathes in heavily through the nose. Fog lifting: yes. The guest lecture at the Uni, voices of those students still lashing the insides his skull. Jago searches a foothold for memory. Faint whiff of tiare, plumeria: airport posters with not-so-secret voluptuous bodies. Why is he alone? Or, not exactly alone.